(untitled) (Research, Society and Development, 2022)
Syphilis is a major public health problem worldwide and affects individuals at various stages of their life cycle. In men, despite the serious consequences to their health, the biggest concern is related to infected women in the reproductive period, due to the potential maternal-fetal risks that such infection could bring. Objective: to identify national and international scientific productions that address syphilis in men. Method: an integrative review, conducted from July to August 2017 by two interdependent researchers, who used MEDLINE, Embase, CINAHL, Cochrane Library, Web of Science, CAPES Journal Portal, and the Virtual Health Library for data collection. Data analysis was based on three thematic units. Results: 18 articles that met the objectives of the study were selected. Of these, most (66.7%) had a quantitative approach, published from 2011 onwards. Discussion: men who have sex with men (MSM) have proven to be a population that is more vulnerable to infection. Obstacles related to diagnosis and treatment were found, as well as the health implications of syphilis in men for women and children. Strategies such as campaigns and the expansion of diagnostic testing were seen as positive. Conclusion: there is a gap in studies on the subject, which highlights the need to invest in new research that discusses the cultural and social aspects of syphilis in men, in order to demystify issues related to sexuality and health care for men.